Quantum semiconductor structures : fundamentals and applications - Weisbuch, C. (Claude), 1945- (Academic Press, 1991)
In its original form, this widely acclaimed primer on the fundamentals of quantized semiconductor structures was published as an introductory chapter in Raymond Dingle's edited volume (24) of Semiconductors and Semimetals. Having already been praised by reviewers for its excellent coverage, this material is now available in an updated and expanded "student edition." This work promises to become a standard reference in the field. It covers the basics of electronic states as well as the fundamentals of optical interactions and quantum transport in two-dimensional quantized systems. This revised student edition also includes entirely new sections discussing applications and one-dimensional and zero-dimensional systems